Controlled deficit irrigation on growth variables of Pennisetum purpureum x Pennisetum typhoides - Chavarría, Jesús; Razz, Rosa; Vilchez-Perozo, Jorge (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Currently, efficiency in water use in agriculture is being sought through techniques that allow for the reduction of the water footprint of crops. This is why the effect of controlled deficit irrigation on the growth variables of King Grass Morado (Pennisetum purpureum x Pennisetum typhoides) was evaluated in the canton of Chone, Ecuador. The treatments studied were: irrigation levels at 40, 60, 80, and 100 % of the crop evapotranspiration (ETc). The grass was sown in black polyethylene bags with a capacity of 10 kg of soil. A completely randomized experimental design with repeated measures over time was used, along with five replicates. The results obtained from the Friedman test showed significant differences (p<0.0001) due to the effects of the study factors: deficit irrigation and successive cuts of the grass on the net assimilation rate of the grass (TAN), growth rate (TC), relative growth rate (TCR), and leaf area index (IAF) did not occur in the same way for the interaction between them. When the irrigation sheet is applied at 80 % of ETc, the TC is better at 0,0002409 g.(dm2.d)-1, TCR is -0,00022 g.g.d-1, and TAN is 0,0072065 g.(dm2.d)-1. The leaf area index performs best with the irrigation sheet at 100 % of ETc with 1,81. King Grass Morado can reduce its actual water requirement by up to 80 % without being affected in growth variables.